Professional C# 2012 and net 4.5 (John Wiley& Sons, Inc., Indianapolis, Indiana, 2013)
Covers challenging .NET features including Language Integrated Query (LINQ), LINQ to SQL, LINQ to XML, WCF, WPF, Workflow, and Generics Puts the new Async keyword to work and features refreshers on .NET rchitecture, objects, types, inheritance, arrays, operators, casts, delegates, events, strings, regular expressions, collections, and memory anagement Explores new options and interfaces presented by Windows 8 development, WinRT, and Metro style apps Includes traditional Windows forms programming, ASP.NET web programming with C#, and working in Visual Studio 2012 with C#